Using podcasts to deliver pediatric educational content: Development and reach of PediaCast CME. (February 2019) - Patrick, Michael D.; Stukus, David R.; Nuss, Kathryn E.
Objective: Pediatricians have used podcasts to communicate with the public since 2006 and medical students since 2008. Previous work has established quality criteria for medical education podcasts and examined the benefit of offering continuing medical education (CME) credit for online activities. This is the first descriptive study to outline the development and reach of a pediatric podcast that targets post-graduate healthcare providers, enhances communication by incorporating quality criteria, and offers free accredited CME to listeners. Methods: We produced 26 podcast episodes from March 2015 to May 2017. Episodes incorporated quality criteria for medical education podcasts and offered free CME credit. They were published on a website, available for listening on multiple digital platforms and promoted through several social media channels. Data were analyzed for frequency of downloads and geographic location of listeners. Results: The cumulative total of episode downloads was 91, 159 with listeners representing 50 U.S. states and 108 countries. Podcast listenership grew over time. Individual episodes had their largest number of downloads immediately following release, but continued recruiting new listeners longitudinally, suggesting use of the archive as an "on-demand" source of educational content. Conclusions: Pediatric podcasts that incorporate quality criteria and offer free CME credit can be used to deliver educational content to a large global audience of post-graduate healthcare providers. Since podcast communication is rapidly growing, future work should focus on identifying the professional roles of listeners; exploring listener perceptions of quality, value and satisfaction; and examining podcast impact on knowledge transfer, clinical practice, public policy and health outcomes.